DO DECISION-MAKING PROFESSIONALS COMMIT THE SUNK-COST FALLACY? - Musa Ilias Biala (Malete Journal of Accounting and Finance, 2023)
Decision-making professionals, such as economists, accountants and business majors, are usually taught the general economic principle that when evaluating the costs of a decision, the decision maker should consider only those costs that are actually incurred as a result of making that decision, and that sunk costs should be ignored. However, there has been considerable anecdotal evidence that many of these decision-making professionals honour sunk costs in their decisions. Some studies have provided evidence in support of the anecdotal evidence while some have refuted the evidence. In order to shed more light on this topic, this paper, therefore, examines whether these decision-making professionals too are adversely influenced by sunk costs when making their decisions. By carrying out proportion tests on 156 respondents and estimating a binary logit model for two decision-making vignettes, this study found that the selected professional decision makers committed the sunk cost fallacy, and that the amount (or size) of the sunk cost was a major significant determinant of the susceptibility to sunk-cost fallacy. The study also found that the proportion of professional decision makers who committed the fallacy differed according to the nature of the decision. These findings suggest that having background knowledge about sunk cost does not preclude individuals from committing the fallacy and that susceptibility of a decision maker to sunk-cost fallacy depends on the nature of the decision being made.